2002
DOI: 10.1191/0267659102pf544oa
|View full text |Cite
|
Sign up to set email alerts
|

Levels of inflammatory markers in the blood processed by autotransfusion devices during cardiac surgery associated with cardiopulmonary bypass circuit

Abstract: Intraoperative blood salvage devices allowing a reinfusion of red blood cells (RBCs) after processing of shed blood and stagnant blood in the mediastinal cavity are more and more used to reduce homologous blood requirements in cardiac surgery with cardiopulmonary bypass (CPB). As the proinflammatory activity of the shed blood also contributes to morbidity during CPB, we conducted a prospective study in order to examine the quality of autologous blood before and after processing with five different devices [BRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 27 publications
2
55
1
3
Order By: Relevance
“…This has also been shown in shed blood after orthopedic surgery, where the retransfusion of this blood resulted in proinflammatory alterations in the patient's systemic cytokine profile [30 -32]. Several groups have demonstrated that the use of cell savers reduces the level of inflammatory mediators in shed mediastinal blood [29,33]. Westerberg and colleagues [34] recently reported reduced plasma interleukin-6 and C3a after cardiopulmonary bypass in patients whose cardiotomy suction blood had been discarded.…”
mentioning
confidence: 92%
“…This has also been shown in shed blood after orthopedic surgery, where the retransfusion of this blood resulted in proinflammatory alterations in the patient's systemic cytokine profile [30 -32]. Several groups have demonstrated that the use of cell savers reduces the level of inflammatory mediators in shed mediastinal blood [29,33]. Westerberg and colleagues [34] recently reported reduced plasma interleukin-6 and C3a after cardiopulmonary bypass in patients whose cardiotomy suction blood had been discarded.…”
mentioning
confidence: 92%
“…In addition, it has been demonstrated that recovered blood cells exhibited an improved oxygen carrying capacity and stronger anti-infiltration capacity than stored blood cells, which reduce the incidence of metabolic acidosis and electrolyte imbalance caused by the infusion of a large number of stored blood cells (23). Other studies that compared intraoperative cell salvage with allogeneic blood transfusion have demonstrated an increased mean erythrocyte viability, increased 2,3-DPG (24,25) and increased ATP levels (26,27) in salvaged blood. In the present study, no significant difference in the levels of Na + K + -ATPase, Ca 2+ -ATPase, Mg 2+ -ATPase and 2,3-DPG were observed between pre-operative and recovered RBCs, suggesting that autologous blood transfusion in liver transplantation in patients with hepatitis B and decompensation had no significant influence on the functions of RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…The RBCs are added to normal saline to obtain an HCT between 50% and 60% and are then pumped into a bag ready for transfusion. [6,7] The disposable components for suctioning and collection of blood are supplied separately from the components that perform further processing into washed packed cells (Fig. 1).…”
mentioning
confidence: 99%